2016
DOI: 10.1111/jcmm.12893
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal induces cell death through endoplasmic reticulum stress‐associated ROS production and mitochondrial dysfunction

Abstract: Diabetic retinopathy (DR) and age-related macular degeneration (AMD) are two important leading causes of acquired blindness in developed countries. As accumulation of advanced glycation end products (AGEs) in retinal pigment epithelial (RPE) cells plays an important role in both DR and AMD, and the methylglyoxal (MGO) within the AGEs exerts irreversible effects on protein structure and function, it is crucial to understand the underlying mechanism of MGO-induced RPE cell death. Using ARPE-19 as the cell model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 58 publications
4
53
0
Order By: Relevance
“…The death‐inducing ability of anticancer compounds has to do with ROS production and its capacity to induce ERS . Simultaneously, the presence of ROS and ERS stimulates the presentation of different damage‐associated molecular patterns, which can result in the death of cancer cells by different mechanisms .…”
Section: Resultsmentioning
confidence: 99%
“…The death‐inducing ability of anticancer compounds has to do with ROS production and its capacity to induce ERS . Simultaneously, the presence of ROS and ERS stimulates the presentation of different damage‐associated molecular patterns, which can result in the death of cancer cells by different mechanisms .…”
Section: Resultsmentioning
confidence: 99%
“…Methylglyoxal, a metabolite increased in diabetes, induces cell death through endoplasmic reticulum stress–associated ROS production and mitochondrial dysfunction . It is associated with insulin resistance, vascular dysfunction, and neuropathies [7c].…”
Section: Discussionmentioning
confidence: 99%
“…Through testing the membrane potential, we found that the exposure to MGO markedly decreased ΔΨm levels, evidenced by a weak green fluorescence in the cells, indicating mitochondrial injury. Ray et al showed MGO inhibits electron flow through complex I leading to mitochondrial dysfunction [33, 34]. In addition, some reports revealed that AGEs can also trigger mitochondrial dysfunction [35, 36].…”
Section: Discussionmentioning
confidence: 99%